Strategi Komunikasi Interpersonal dalam Meningkatkan Kepercayaan Donatur terhadap Program Yayasan Grandma’s Foundation (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
This Community Service Activity (PKM) aims to strengthen interpersonal communication strategies in increasing donor trust in the Grandma Foundation as a social institution engaged in elderly services. The main problems identified include communication patterns that are not systematic, lack of personalization, and lack of transparency of information, so that it has an impact on the level of trust and loyalty of donors. Through a qualitative-educational-participatory approach, PKM activities are carried out through the delivery of effective communication materials, interpersonal communication simulations, the preparation of donor communication flow standards, and assistance in digital communication practices based on social media and instant messaging. The results of the activity showed a significant increase in the attitude and communication skills of the management, the formation of donor communication operational standards, the improvement of digital communication skills, and the positive response from donors which was reflected in the increase in interaction and trust. These findings confirm that interpersonal communication based on empathy, transparency, and consistency plays an important role in building long-term relationships with donors. Thus, a structured interpersonal communication strategy can be an effective model for philanthropic institutions in managing donor relationships and maintaining the sustainability of social programs.